(untitled) (Bangladesh Journal of Pharmacology, 2025)
In triple-negative breast cancer, intratumoral hypoxia drives tumor progression via HIF-1α-mediated angiogenesis. The study aims to analyze the efficacy of berberine chloride on tumor proliferation and angiogenesis in triple-negative breast cancer mediated by HIF-1α. The triple-negative breast cancer cells were subjected to berberine chloride, and the effects on cell viability, apoptosis, and angiogenic gene expression were assessed. MTT assay determined the IC50 as 9.5 µM. Fluorescent imaging confirmed apoptosis through membrane disintegration, fragmented DNA, and the presence of apoptotic bodies. Real-time PCR analysis showed significant down-regulation of HIF-1α (p<0.01), VEGF (p<0.05), Ang1 (p<0.05), and Ang2 (p<0.01) after berberine chloride treatment. These findings indicate the efficacy of berberine chloride in inhibiting triple-negative breast cancer cell proliferation and angiogenesis, highlighting its potential as a therapeutic candidate.